2021
DOI: 10.1002/jgc4.1413
|View full text |Cite
|
Sign up to set email alerts
|

Financial constraints on genetic counseling and further risk‐management decisions among U.S. women at elevated breast cancer risk

Abstract: Clinical guidelines recommend that women at high risk of breast cancer should consider various risk-management options, which remain widely underutilized. We conducted semi-structured, qualitative interviews with 50 high-risk women to understand how financial constraints affect use of genetic counseling, genetic testing, and further risk-management decisions. Inductive analyses revealed three categories of health-related financial constraint: (a) lack of insurance, (b) underinsurance, and (c) other financial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Enhanced surveillance methods can substantially improve early detection of breast cancer when treatment is most effective; prophylactic surgeries and medication can reduce breast cancer risk by 40%–95% 1,4 . Yet, these options are substantially underused due to lack of systematic risk screening and support in cancer risk‐management decision‐making in the United States 3,5–7 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced surveillance methods can substantially improve early detection of breast cancer when treatment is most effective; prophylactic surgeries and medication can reduce breast cancer risk by 40%–95% 1,4 . Yet, these options are substantially underused due to lack of systematic risk screening and support in cancer risk‐management decision‐making in the United States 3,5–7 …”
Section: Introductionmentioning
confidence: 99%
“…1,4 Yet, these options are substantially underused due to lack of systematic risk screening and support in cancer risk-management decision-making in the United States. 3,[5][6][7] Numerous breast cancer risk prediction models have been developed. 8,9 In the United States, the Gail, Claus, and IBIS (i.e., Tyrer-Cuzick) models are commonly used in research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent study published in the Journal of Genetic Counseling , barriers to care for women with a high risk of breast cancer include a multitude of cost‐associated factors, even when those patients are covered by health insurance 1 . The findings illustrate a critical need for health care pricing transparency to detect and treat cancer early.…”
mentioning
confidence: 99%
“…Qualitative interviews were conducted with 50 female patients to assess various aspects of financial constraints, including a lack of medical insurance, underinsurance, and other miscellaneous factors such as the management of comorbidities and medical debt. Several characteristics were examined, including age, race (60% White and 40% Black), breast cancer risk, income and education levels, health insurance and employment status, marital status, and number of household members 1 . Researchers found that financial considerations were complex in patients' management of elevated risk.…”
mentioning
confidence: 99%